Diversity of blackgram (Vigna mungo L. Hepper) genotypes assessed through morphological and biochemical approaches - Gantait, Saikat; Mandal, N.; Das, P. K. (Journal of Tropical Agriculture, 2009)
Morphological and seed protein variations in 12 blackgram genotypes from the eastern, northern, and southern parts of India were assessed. The morphological response of the genotypes over two years (2006 and 2007) in four consecutive environments (rabi and pre-kharif) revealed three clusters with overlapping genotypes. Five clusters obtained through SDS-PAGE seed protein analysis expressed better grouping of genotypes. The clustering pattern, however, did not reflect the geographical distribution of genotypes.